Hurting on the inside girls and bullying - Beaumont, Rosie; Leigh, Richard; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2001)
This program looks at how girls bully, why they bully and how it can be addressed successfully. We also address issues facing the person being bullied
Title from title screen
Executive producer, Neil Barrett ; graphics, Reece Sanders ; editor, Simon Wright ; camera, Adis Hondo, Walter Repich, Lee Tilson
Keywords: Bullying; Bullying in schools